Legal Approach to the Sale of Imported Second-Hand Clothing in Stores to Protect Consumers - Refangga, Galih Setyo; Sujiantoro, Hibertus; Febriana, Linda (PT FORMOSA CENDEKIA GLOBAL, 2024)
Certain individuals in Indonesia have started to participate in the trade of selling second-hand clothing imported from nearby nations. For certain individuals, this location serves as a means of making a livelihood by engaging in the trade of purchasing and selling second-hand imported garments. According to Article 47, paragraph (1) of Law Number 7 of 2014 on Trade, it is mandated that all importers must bring in items in a brand new condition. In addition to the implementation of Minister of Trade law Number 40 of 2022, which specifically states and mandates the destruction of imported used apparel that is being sold in Indonesia after the law comes into effect